Sharia Financing Administration System at BMT PETA - Bekti Widyaningsih; Varizka Alzana Rahma (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Indonesia is a country that has the potential for the development of high economic value, one of which is in the business sector or the business sector. Business is an activity carried out by organizations or individuals covering production, buying and selling activities, which can also be in the form of exchanging goods or services, with the aim of gaining profit or profit. Components of business implementation required administration. Administration is part of the most important system in business which includes efficiency, effectiveness, rationality. Sharia financing is an activity in the form of providing funds and goods from the bank to customers according to an agreement that requires the party being financed to return the funds after a certain period of time according to the agreement agreed at the beginning of the agreement with rewards or profit sharing based on sharia principles, namely by using the principle mudharabah, musyarakah, murabahah and ijarah. One of the institutions implementing sharia financing is the Baitul Maal Wat-Tamwil Tasyrikah Agung Economy (BMT PETA). BMT PETA is an Islamic-based non-bank financial institution founded by the Pesulukan Agung Tulungagung Islamic boarding school with the aim of strengthening the congregation's economy from the Peta Islamic boarding school itself or the wider community. The financing carried out by BMT PETA is financing that can be used for trading business capital, capital for farmers, capital for purchasing motorized vehicles, educational capital, and capital to meet personal needs.